Non-scribal Communication Media in the Bronze Age Aegean and Surrounding Areas The semantics of a-literate and proto-literate media (seals, potmarks, mason's marks, seal-impressed pottery, ideograms and logograms, and related systems) - Jasink, Anna Margherita; Weingarten, Judith; Ferrara, Silvia (Strumenti per la didattica e la ricerca, 2017)
This volume is intended to be the first in a series that will focus on the origin of script and the boundaries of non-scribal communication media in proto-literate and literate societies. Over the last 30 years, the domain of scribes and bureaucrats has become much better known. Our goal now is to reach below the élite and scribal levels to interface with non-scribal operations conducted by people of the «middling» sort. Who made these marks and to what purpose? Did they serve private or (semi-) official roles in Bronze Age Aegean society? The comparative study of such practices in the contemporary East (Cyprus, Anatolia, the Levant, and Egypt) can shed light on sub-elite activities in the Aegean and also provide evidence for cultural and economic exchange networks